Beyond the Graven Image - Kochan, L. author. aut Link
VI, 223 p.
Keywords: The biblical prohibition of images sets Judaism apart, together with Islam, from all other religious systems. This book attempts to explain the reasons for the prohibition - as well as its limits - and then shows how influential it has been in determining aspects of Jewish thinking in relation to such key concepts as holiness, symbolism, mediation between man and God, aesthetics and the role of memory in religion. Why is music the one art to which Judaism is hospitable? Is Judaism a religion of the ear rather than the eye? What is the real issue at stake in the age-old debate between Jerusalem and Athens? How do these issues relate to the iconoclastic movements in Byzantine Christianity and the Reformation? Lionel Kochan makes clear that to the prohibition of the graven image there is more than meets the eye.